Elementary Students Learn English Through the Pedagogical Implementation of Short Stories (2024)
This study investigates the impact of implementing a pedagogical approach to teaching English as a Foreign Language (EFL) through short stories in post-COVID times with fifth-grade students at a private school in Bogota, Colombia. The research, conducted during quarantine, utilizes a descriptive qualitative methodology, analyzing data collected through surveys, class artifacts, and class newspapers. The study emphasizes the dynamic and multifaceted nature of the language acquisition journey for EFL students, especially when utilizing short stories as a teaching tool. Short stories are seen as effective vehicles for language learning, providing a contextualized and authentic platform for students to engage with language in real-life contexts. This immersion enhances understanding of vocabulary, grammar structures, and idiomatic expressions, while the narrative format facilitates a more intuitive grasp of linguistic nuances. Additionally, the implementation of short stories encourages active language use through reading, discussion, and the creation of narratives by students. This participatory element not only reinforces language skills but also promotes creativity and critical thinking. The study suggests that short stories offer insights into cultural and social dimensions of language, allowing students to learn not only language rules but also gain understanding of cultural contexts, societal norms, and diverse perspectives embedded in the narratives. This cultural immersion contributes to a more comprehensive and authentic language learning experience. In conclusion, the implementation of short stories in EFL classrooms is presented as a dynamic pedagogical strategy, creating a rich and immersive language learning environment. This approach aims to enhance linguistic competence while fostering a holistic understanding of language within its cultural and social contexts.